Tinjauan Kualitas Pelayanan Pasien JKN Non PBI di Instalasi Rawat Jalan Puskesmas Batua Kota Makassar - Leni Karunia Septiani; Nanda Aula Rumana; Deasy Rosmala Dewi; Noor Yulia (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Service quality comes from the comparison of what consumers feel (expectations) with consumer perceptions about the performance of companies that provide services. The purpose of this study was to describe the quality of service for JKN non-PBI patients at the Batua Public Health Center in Makassar. The method used is quantitative analysis with descriptive method. Calculation of sample size using the proportion estimation formula obtained 96 samples with the sampling method, namely Incidental/Convenience Sampling. Data collection techniques using interviews and self-filling by patients with interview guide instruments and questionnaires, and data were analyzed using SPSS. Service quality is assessed based on 5 dimensions, namely Tangible, Responsiveness, Reliability Assurance and Empathy. From the results of the study, it was found that the percentage of service quality at Batua Health Center was 57.3% of good service quality and 42.7% not good, meaning that the service quality was classified as not good because ≤ 90% based on outpatient SPM. Obstacles that often occur when serving patients such as problems with communication tools/speakers, lack of computers, patients do not want to queue and do not bring medical cards/BPJS cards/identity cards. It is recommended to the Puskesmas to pay more attention to the cleanliness and comfort of the registration place, the officers should improve their competence, advance working hours so that there are no delays in opening the counter, apply 3S 1T, pay attention to the problematic speakers and computers as well as socialize the files that must be brought during registration.